FRI0214 Six-Year Retention Rate of Abatacept in Rheumatoid Arthritis: A Multicentric Retrospective Analysis. (15th July 2016) - Favalli, E.G.; Botsios, C.; Bazzani, C.; Raffainer, B.; Ciancio, G.; Giollo, A.; Marchesoni, A.; Gorla, R.; Caimmi, C.; Becciolini, A.; Crotti, C.; Piantoni, S.; et al.
Abstract : Background: Abatacept (ABT) short-term efficacy and safety profile in the treatment of rheumatoid arthritis (RA) is well established and supported by randomised controlled trials. However, data on ABT long-term effects are still lacking and reported drug survival analyses are often limited to no more than 2-year follow-up. Objectives: The aim of the study is to evaluate in a real-life scenario the overall 6-year retention rate of ABT in the treatment of RA and to compare its survival rate as first or second line biotherapy. Methods: Data were retrospectively extracted from six local registries including all RA patients treated with ABT between January 2008 and April 2015. The analysis was limited to patients treated with ABT as first or second line biologic agent. The 6-year retention rate was calculated by Kaplan-Meier method and the comparative risk for discontinuation between the two lines of treatment was compared by a stratified log-rank test. Results: 236 RA patients (78.5% female, mean age [± standard deviation, SD] 57.6 [±12.7] years, mean disease duration 14.3 [±13.4] years, positive rheumatoid factor 82.2%, positive anti-citrullinated peptide antibodies 71.1%, mean DAS28 5.19 [±1.2]) were retrospectively enrolled. 83 patients were treated with ABT as first-line biotherapy, whereas 153 were second-line users. The overall retention rate was 63.7% at 3 years and 61.8% at 6 years. The 6-year retention rate was significantly higher in the first-line compared with the second-line therapy group (68% and 61.8%, respectively; p=0.04). Overall, ABT was discontinued in 69 (29.2%) patients. Twenty-one (8.9%) patients (4 first-line and 17 second-line users, p=0.15) withdrew ABT because of adverse events, whereas 41 (17.4%) patients (10 first-line and 31 second-line users, p=0.1508) stopped the therapy because of primary or secondary inefficacy. Seven (2.7%) patients discontinued ABT because of other reasons (i.e. lost at follow-up, pregnancy and remission) and were excluded from the retention analysis. Conclusions: In our multicentric experience the 6-year retention rate of both first and second line ABT was about 60%. Used as first line ABT showed a significantly higher survival on treatment compared with the second line. Moreover, ABT demonstrated an overall favourable safety profile, with a very low occurrence of adverse events leading to discontinuation. Disclosure of Interest: None declared